2015
DOI: 10.1002/jmv.24336
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis E virus antibodies among blood donors in Southern Brazil

Abstract: Brazil has been classified as moderately endemic for hepatitis E virus (HEV) infection. However, data on the seroprevalence of HEV in this region are limited. This study evaluated the prevalence of past or present HEV infection among blood donors in the metropolitan area of Itajai Valley, Southern Brazil, a region of predominant German heritage, where cultural habits result in a high consumption of pork. Serum samples from 300 blood donors were tested in December 2014 using serological and molecular methods. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
2
28
1
7
Order By: Relevance
“…The performance of anti‐HEV IgG assays may have played a role in the higher seroprevalence of anti‐HEV antibodies found in recent studies . Two different studies, both in blood donors, one in Southern Brazil (10%) and other in Southeastern Brazil (9.8%) found similar prevalence to that reported in this study . Both of them used the same high sensitivity commercial anti‐HEV assays contributed to the similar detection of anti‐HEV rates to those observed in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The performance of anti‐HEV IgG assays may have played a role in the higher seroprevalence of anti‐HEV antibodies found in recent studies . Two different studies, both in blood donors, one in Southern Brazil (10%) and other in Southeastern Brazil (9.8%) found similar prevalence to that reported in this study . Both of them used the same high sensitivity commercial anti‐HEV assays contributed to the similar detection of anti‐HEV rates to those observed in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Currently, data about seroprevalence of HEV infection in Brazil are improving and showing increase of the prevalence . The performance of anti‐HEV IgG assays may have played a role in the higher seroprevalence of anti‐HEV antibodies found in recent studies .…”
Section: Discussionmentioning
confidence: 99%
“…Blood donors were from the North region of Rio Grande do Sul state, a region with a high density of pigs farms and high consumption of pig meat and related products. Amongst the samples analyzed, 314 (40.25%) had antibodies to HEV, a prevalence much higher than that reported recently in a neighboring state [43] or other countries. Even though differences in the ELISA settings and sensitivity of the assay might account for differences in the percentile of seropositive found amongst different studies [44] we credit the higher percentile of seropositive samples to characteristics inherent to the population studied and to the geographical localization.…”
Section: Discussionmentioning
confidence: 61%
“…This country has been classified as moderately endemic for HEV, with seroprevalence from 1% to 4% in blood donors or the general population, 13% in individuals from an agricultural settlement in the Amazon Basin, and 15% in renal transplant recipients 10, 11, 12, 13. A more recent study observed a seroprevalence of anti-HEV IgG antibodies of 10% among blood donors in the metropolitan area of Itajai Valley, Southern Brazil, a region of predominant German ancestry where cultural habits result in a high pork consumption 14 . Genotype HEV-3 infection has been described in the country, both among immunocompetent and immunocompromised individuals 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%